Quantification of weekly external load in female futsal players: considering inter-day and -player variability - Spyrou, K.; Ribeiro, J. N.; Alcaraz, P. E.; Freitas, T. T.; Travassos, B. (Research Quarterly for Exercise and Sport, 2025)
This study aimed to analyze weekly training external load and match demands in female futsal players. Eight players competing in the 2nd Division of Spain, were recruited. Training and match load data, including total, low- medium- high-intensity accelerations (ACC), decelerations (DEC), and changes of direction (COD) were recorded and analyzed considering total effective time. A linear mixed model was used. Significantly more ACC and COD, and total and low-intensity DEC actions occurred on match day (MD), MD-4 and MD-2 compared to MD+2 (p = <.001-0.04; ES = 0.56-1.79). No differences were found between MD and MD-4 (p = 0.293-1.000; ES = 0.00-0.71). Significantly more total ACC and total and low-intensity DEC occurred on MD than MD-2 (p = 0.014-0.021; ES = 0.29-0.55), and total DEC and COD on MD-4 than MD-2 (p = 0.001-0.017; ES = 0.28-0.89). Moderate-high inter-day and -player variability was found. The microcycle periodized based on MD, revealing inter-day and individual variability in external load.